Erectile Dysfunction Among Patients with Hypertension and AssociatedSocio-Demographic Factors - Satti, Raja Rizwan Ul Haq; Rasheed, Syed Abdul; Gul, Rubab; Athar, Muhammad Hammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of erectile dysfunction among the patients of hypertension and analyze the associated socio demographic factors. Study Design: Cross sectional analytical study. Place and Duration of Study: Medicine Department, Pak Emirates Military Hospital Rawalpindi, from Aug to Oct 2018. Methodology: Two hundred and five married male patients of hypertension diagnosed for more than one year by a consultant medical specialist were included in the study by non-probability consecutive sampling. Erectile dysfunction (ED) was assessed by using the International Index of Erectile Function-5 (IIEF-5). Socio-demographic factors in the study included age, education, smoking, poly-pharmacy and duration of illness. Results: Out of 205 patients of hypertension, 95 (46.3%) patients had no ED, 57 (27.8%) patients had mild, 17 (8.3%) patients had moderate and 12 (5.2%) patients had severe ED. Mean age of the study participants was 39.94 ± 4.14 years. Mean duration of hypertension among the patients in this study was 6.24 ± 2.78 years. Increasing age, tobacco smoking, poly-pharmacy and long duration of illness had statistically significant association with ED (p-value <0.05) while education was not found significantly associated in our study. Conclusion: There was a high frequency of erectile dysfunction among the patients suffering from hypertension. Special attention should be paid on individuals with advancing age and long duration of illness. Tobacco smoking should be discouraged and poly-pharmacy if, possible should be avoided among the patients suffering from hypertension and ED.